The degree of the secondary school teacher using the Madrasati platform in education in Al-Baha region - AlRobai, Fahed Salem; Al Sofran, Muhammad Hassan (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the degree of secondary school teachers’ use of the Madrasati platform in education in the Al-Baha region in the Kingdom of Saudi Arabia, and to identify the obstacles to its use in education. The descriptive approach was used, and the study tool consisted of a questionnaire consisting of (31) items distributed on three axes. It was applied to a sample of (100) secondary school teachers, and the study concluded that the degree of secondary school teachers’ use of the Madrasati platform in general is high, with an arithmetic mean of (3.4). As a platform for education to a large extent and with an arithmetic mean (3.9), The study also found a number of proposals to activate the use of secondary school teachers for the Madrasati platform in education, and presented appropriate recommendations in the light of the research results.